DETERMINING THE TIME OF A VESSEL´S SINGLE VOYAGE UNDER THE TERMS OF A VOYAGE CHARTER-PARTY - Koskina, Yu. O. (Systems and Technologies, 2025)
The paper is devoted to the procedure for determining the elements and total voyage time in accordance with the terms of a voyage charter-party. The basis for the performance of a voyage for the carriage of goods by a tramp vessel is a voyage charter party concluded between the shipowner-carrier and the charterer, which is in essence a contract for the carriage of goods. The terms of such a contract largely determine the duration of the voyage, which for the shipowner-carrier is a certain benchmark for the employment of the vessel under the contract concludede and for the charterer allows to estimate the time of cargo trans- portation on the sea leg of its delivery. The paper considers a single voyage of a vessel, which is carried out on the terms “1 port of loading – 1 port of discharg- ing”. The voyage of a vessel is considered in the paper as consisted of separate components – a ballast passage (if necessary), the vessel is at the port of loading, passage with cargo and staying at the port of discharging. The procedure for their calculation is presented with reference to the terms of the voyage charter party, which are used in the relevant calculations as initial data. Among these terms, the ports of loading and unloading are of fundamental importance for determining the duration of the ves- sel's passages, as far as they determine the distance of the vessel's passages with cargo and also the route of the voyage. It is emphasized the importance of considering the terms of the voyage charter party regarding the timing of the vessel's arrival at the port of loading, as specified in the voyage charter party by the laydays and cancelling dates. When calculating the time a vessel is at berth in ports for the relevant cargo operations, the cargo operations rates agreed in the voyage charter party, the procedure for counting days off and holidays, and the terms for begining the laytime running are of great importance. The varied wording of these terms of the voyage charter party may require certain adjustments, but the basic procedure for calculating the duration of the elements and the total voyage time remains unchanged.